2017
DOI: 10.1099/jmm.0.000407
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of culture-dependent and culture-independent molecular methods for characterization of vaginal microflora

Abstract: We found little overlap between the species found using cultivation-dependent and cultivation-independent methods. Rather, culture-dependent and culture-independent methods were found to be complementary in describing the vaginal microflora among South Indian women. Culture-independent methods were found to be superior in detecting clinically relevant vaginal flora.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Moreover, in order to obtain more information, a cultural-dependent approach was combined with a cultural-independent molecular method. According to Pandya et al (2017) these techniques seem to be roughly equivalent and, when used in parallel, it is possible to obtain best results leading to major advances in the reliable knowledge of microbial populations living in an environment. The cultural results were confirmed by the HTS analysis that showed an increase in bacterial families belonging to Clostridiales order, such as Tissierellaceae and Clostridiaceae , which represented the most abundant bacterial taxa until the end of the incubation time.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in order to obtain more information, a cultural-dependent approach was combined with a cultural-independent molecular method. According to Pandya et al (2017) these techniques seem to be roughly equivalent and, when used in parallel, it is possible to obtain best results leading to major advances in the reliable knowledge of microbial populations living in an environment. The cultural results were confirmed by the HTS analysis that showed an increase in bacterial families belonging to Clostridiales order, such as Tissierellaceae and Clostridiaceae , which represented the most abundant bacterial taxa until the end of the incubation time.…”
Section: Discussionmentioning
confidence: 99%
“…Not many studies have been conducted on which sampling method is favorable for sequence-based diagnostic techniques. Regardless of how the sample is acquired, culture-dependent and molecular sequencing-based techniques have been shown to isolate different types of Lactobacilli in different amounts in women (10,25,44). A comparative study in healthy mares showed that there is no significant difference in the sequence-based results found between different sampling techniques: double-guarded endometrial swab, low-volume lavage, or endometrial biopsy (26).…”
Section: Sequence-based Techniquesmentioning
confidence: 99%
“…Since the 1800s, physicians and researchers investigate the vaginal bacterial community using both cultivation and culture‐independent methods (Pandya et al., ; Srinivasan et al., ). To date, many species from the vaginal microbiota have been identified.…”
Section: Introductionmentioning
confidence: 99%